2019
DOI: 10.1214/18-aop1286
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative random permutations of integers

Abstract: Motivated by recent studies of large Mallows(q) permutations, we propose a class of random permutations of N+ and of Z, called regenerative permutations. Many previous results of the limiting Mallows(q) permutations are recovered and extended. Three special examples: blocked permutations, p-shifted permutations and p-biased permutations are studied.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 96 publications
(138 reference statements)
0
48
0
Order By: Relevance
“…Residual allocation models with other choices of parameters for the U i 's with different beta distributions are found in [29,37]. Much effort has been devoted to the occupancy scheme, known as the Bernoulli sieve, which is based on a homogeneous residual allocation model (1), that is, with independent and identically distributed (iid) factors U i having arbitrary distribution on (0, 1), see [2,16,22,27,28,34]. The homogeneous model has a multiplicative regenerative property, also inherited by the partition of the set of balls.…”
Section: Introductionmentioning
confidence: 99%
“…Residual allocation models with other choices of parameters for the U i 's with different beta distributions are found in [29,37]. Much effort has been devoted to the occupancy scheme, known as the Bernoulli sieve, which is based on a homogeneous residual allocation model (1), that is, with independent and identically distributed (iid) factors U i having arbitrary distribution on (0, 1), see [2,16,22,27,28,34]. The homogeneous model has a multiplicative regenerative property, also inherited by the partition of the set of balls.…”
Section: Introductionmentioning
confidence: 99%
“…Our inspiration comes from the rainstick process. It was introduced by Pitman and Tang in [11] with followup work by Pitman, Tang and Duchamps [4]. In this discrete time process raindrops fall one after the other on the positive integers and sites become wet when landed on.…”
Section: Introductionmentioning
confidence: 99%
“…Let T be the first time that the configuration is a single wet component containing 1, and let K be its length. Pitman and Tang observed in [11] that the value of K describes the size of the first block in a family of regenerative permutations. Understanding block sizes has been useful for studying the structure of random Mallows permutations [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…u k = P ∩ k i=1 (U j ∈ I i for some 1 ≤ j < n(k, 1)) (1.5) and we adopt the convention that u 0 := 1. This sequence (u k , k ≥ 0) is a renewal sequence appearing in the study of regenerative permutations in [51]. In that context it is easily shown that the limit u ∞ := lim k→∞ u k exists, but difficult to evaluate the u k for general k. However, computation of u k for the first few k = 1, 2, 3, .…”
Section: Introductionmentioning
confidence: 99%